2017
DOI: 10.1111/aor.12904
|View full text |Cite
|
Sign up to set email alerts
|

Novel ECG-Synchronized Pulsatile ECLS System With Various Heart Rates and Cardiac Arrhythmias: An In Vitro Study

Abstract: The objective of this study is to evaluate electrocardiography (ECG)-synchronized pulsatile flow under varying heart rates and different atrial and ventricular arrhythmias in a simulated extracorporeal life support (ECLS) system. The ECLS circuit consisted of an i-cor diagonal pump and console, an iLA membrane ventilator, and an 18 Fr arterial cannula. The circuit was primed with lactated Ringer's solution and packed red blood cells (hematocrit 35%). An ECG simulator was used to trigger pulsatile flow and to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 18 publications
(26 reference statements)
1
11
0
Order By: Relevance
“…Indeed, THE and SHE levels decreased with increasing heart rate and assist ratio with pulsatile amplitudes of 1000-3000 rpm for all flow rates. Our data from previous studies regarding ECG-synchronized pulsatile flow for adult ECLS support this finding (10,15). However, the results of the present study showed that the i-cor pump significantly increased SHE levels under a pulsatile amplitude of 4000 rpm at 200 mL/min and heart rates of 120 bpm (R1:2) and 150 bpm (R1:3), as well as at 400 mL/min and a heart rate of 120 bpm (R1:2).…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, THE and SHE levels decreased with increasing heart rate and assist ratio with pulsatile amplitudes of 1000-3000 rpm for all flow rates. Our data from previous studies regarding ECG-synchronized pulsatile flow for adult ECLS support this finding (10,15). However, the results of the present study showed that the i-cor pump significantly increased SHE levels under a pulsatile amplitude of 4000 rpm at 200 mL/min and heart rates of 120 bpm (R1:2) and 150 bpm (R1:3), as well as at 400 mL/min and a heart rate of 120 bpm (R1:2).…”
Section: Discussionsupporting
confidence: 86%
“…By syncing a pump's pulsatile waveform with ECG of the patient, it is possible that pulsatile flow pumps, like the i‐cor system, may be able to avoid some of these serious complications. Additionally, other studies have shown improvements in hemodynamic energy transmission, coronary blood flow, and end organ protection when using pulsatile flow ECLS systems . Therefore, there may be specific instances where using pulsatile flow systems may render more physiological benefits, especially for higher risk adult ECLS patients.…”
Section: Discussionmentioning
confidence: 99%
“…We intentionally did not include the results from this particular diagonal pump in the materials and methods section of this manuscript, as it has not been approved by the FDA for clinical practice in the United States. The i‐Cor DP3 diagonal pump is also capable of providing pulsatile flow in addition to conventional non‐pulsatile flow . In addition, the i‐Cor pump is capable of providing ECG‐synchronized pulsatile flow by syncing the pulses of the pump with the patient’s native heartbeat.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pulsatile flow during acute or chronic mechanical circulatory support for pediatric or adult patients is one of the major research areas at the Penn State Hershey Pediatric Cardiovascular Research Center. [16][17][18][19] The predecessor of the PediMag centrifugal pump was the Levitronix PediVAS system, which is capable of generating pulsatile flow and has been tested in an experimental setting at our research center. This pulsatile module was intended for experimental use only and has not been approved by the Food and Drug Administration (FDA) for use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation